Explicit and Implicit Hopelessness and Self‐injury. Issue 3 (26th February 2021) - Gray, Nicola Susan; Knowles, James; George, Danielle; Harvey, Alex; Powell, Rachel; Zadeh, Mehrnaz Vazirian; Wansing, Carlotta; Snowden, Robert J.
Abstract: Objective: This study examined the relationship between explicit and implicit measures of hopelessness and self‐injurious behavior (defined here as self‐harming or suicidal actions and thoughts). Method: A community sample of 267 participants completed explicit measures of hopelessness (Beck's Hopelessness Scale and a Feeling Thermometer), an implicit measure of hopelessness (Hopelessness Implicit Association Test), and a self‐report measure of their history of self‐injurious behavior. Results: The results showed that high levels of hopelessness, measured both explicitly or implicitly, were associated with a past and recent history of self‐injury. However, there was also an interaction between the implicit and explicit measures such that explicit hopelessness was more strongly predictive of self‐injury in people with high levels of implicit hopelessness. Conclusion: The findings show that the implicit measurement of hopelessness can help predict past and recent self‐injury beyond what explicit measures of hopelessness currently achieve and could be used in the assessment of risk of both self‐harming and suicidal behaviors.